2016
DOI: 10.1200/jco.2015.65.9557
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Noninferiority Trial of Telephone Delivery of BRCA1/2 Genetic Counseling Compared With In-Person Counseling: 1-Year Follow-Up

Abstract: Although telephone counseling led to lower testing uptake, our findings suggest that telephone counseling can be effectively used to increase reach and access without long-term adverse psychosocial consequences. Further work is needed to determine long-term adherence to risk management guidelines and effective strategies to boost utilization of primary and secondary preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 72 publications
3
113
1
Order By: Relevance
“…While face-toface counseling is the traditional clinical delivery model in genetic care, phone counseling has been used increasingly and has been found non-inferior to in-person counseling, at least for BRCA1/2 counseling and disclosure. 6,7 Further data are needed regarding outcomes for a broader range of genetic results and in the context of returning incidentally identified research results. Nonetheless, phone counseling is a practical approach that many are utilizing when face-to-face counseling is not feasible.…”
mentioning
confidence: 99%
“…While face-toface counseling is the traditional clinical delivery model in genetic care, phone counseling has been used increasingly and has been found non-inferior to in-person counseling, at least for BRCA1/2 counseling and disclosure. 6,7 Further data are needed regarding outcomes for a broader range of genetic results and in the context of returning incidentally identified research results. Nonetheless, phone counseling is a practical approach that many are utilizing when face-to-face counseling is not feasible.…”
mentioning
confidence: 99%
“…We describe the Risk, Education, and Assessment for Cancer Hereditary (REACH) trial in detail elsewhere (5,10). Briefly, REACH was a family cluster randomized, two group, equivalency/non-inferiority trial comparing in-person to telephone counseling for women at high risk for BRCA1/2 mutations (NCT01346761).…”
Section: Methodsmentioning
confidence: 99%
“…To address access barriers, genetic counselors are increasingly using alternative counseling delivery methods such as telephone-based counseling (9). Our randomized controlled non-inferiority trial of in-person vs. telephone-based genetic counseling for breast and ovarian cancer survivors at increased hereditary cancer risk (REACH) found that telephone-based counseling was non-inferior on key patient-reported outcomes such as distress and decisional satisfaction (5,10). A secondary aim of the REACH trial was to examine factors associated with genetic testing decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…139 In fact, telephone genetic counseling has been successfully used to increase reach and access to CGRA among a geographically diverse sample of high-risk women, without long-term adverse psychosocial consequences. 43, 140, 141 Furthermore, results from prior studies have demonstrated that telephone genetic counseling may lead to cost savings compared to in person sessions. 141, 142 In parallel, academic medical centers and commercial companies have increasingly started to offer telephone genetic testing options to increase the reach of CGRA services while improving accessibility.…”
Section: Community- and Policy-level Considerations In Genetic Tesmentioning
confidence: 99%